Households Health Expenditure in Interannual Correlation With Public Health Expenditure in Greece - Zikidou, Stavroula; Hadjidema, Stamatina (Frontiers in Public Health, 2020)
The aim of this paper is to investigate the relationship between public and private health expenditure (macroeconomic and microeconomic approach) over time and within recession and austerity period in Greece, in order to find out whether the strict Memorandum health policies pass, influence or go along with health expenditure to the end consumer, i.e. the health services user. In this context, by using econometric tools such as multiple regression and co-integration analysis on the raw micro-data of Household Budget Surveys of 1987/88 till 2018, as well as using data of public expenditure of OECD- Health Statistics 2019, in the STATA vs 13, we examined the actual impact of financial crisis in Greece. Analysis demonstrated that the Greek HHE was rapidly increasing during 1988-2008, when it started decreasing. Furthermore, total Private and total Public Health expenditure seems to have a bidirectional long run relationship and significant co-integration. So, does the public expenditure with the household medical services expenditure and pharmaceuticals. Apart from that, the results indicate that over the years of recession, the monthly household health expenditure decreases, due to the confiscation of middle-class income which led to consumerism restrictions. However, as households are now spending a bigger portion of their shrunken income for health (as health is an inelastic commodity), HHE, as a proportion of total private expenditure, has eventually risen.